A comparison framework on Islamic dress code and modest fashion in the Malaysian fashion industry - Kamarulzaman, Zulina; Shaari, Nazlina (PalArch Foundation, 2020)
The influence of social media trends in the current world has significantly impacted the fashion industry.Hence, the rise of the Islamic fashion culture has expanded to Western countries, which no longer consider Islamic fashion to be dull and boring. Islamic fashion was also constantly misjudged, even by Muslims, as the idea of covering the body and head with a veil or hijab and wearing body-hugging clothes with a bit of exposed hair is accepted as Islamic wear. This indicated a shift of perspective from a conservative to modern culture in Islamic attire, with a lack ofunderstanding of the difference betweenthe two concepts. Therefore, this study identifies the comparison between the Islamic dress code and modest fashion. The analysis performed used the literature review of previous studies over five years, between 2015 and2020, using databases from Google Scholar and Scopus. However, only 15 articles were discussed in this study. The review of past literature was based on the crucial keywords related to this study. Modest fashion, the Islamic dress code, and Islamic fashion in Malaysia was the focus of the keywords research. The study revealed an understanding of the Islamic dress code among past researchers, as Muslims acknowledged the concept of aurahin dressing. Modest fashion, on the other hand, was seen as another fashion movement referring to Muslims,with a combination of religious symbols and modern trends in mainstream clothing brands, together with the marketing strategies of local brand development focusing on the Muslim demographics. The extent to which a dressing style follows the laws of Syariah, or fits the modern culture, or a combination of both, depending on the individual. As such, this study intends to clarify both the concepts for a better understanding of Islamic wear and modest fashion.